The effect of Midazolam and Propranolol on fear memory reconsolidation in ethanol-withdrawn rats: Influence of D-cycloserine - Ortiz, Vanesa (2014)
Background: Withdrawal from chronic ethanol facilitates the formation of contextual fear memory and delays the onset to extinction, with its retrieval promoting an increase in ethanol consumption. Consequently, manipulations aimed to reduce these aversive memories, may be beneficial in the treatment of alcohol discontinuation symptoms. Related to this, pharmacological memory reconsolidation blockade has received greater attention due to its therapeutic potential. Methods: Here, we examined the effect of post-reactivation amnestic treatments such as Midazolam (MDZ, 3 mg/kg i.p) and Propranolol (PROP, 5 mg/kg i.p) on contextual fear memory reconsolidation in ethanol- withdrawn (ETOH) rats. Next, we examined whether the activation of N-methyl-D-aspartate (NMDA) receptors induced by d-cycloserine (DCS, 5 mg/kg i.p., a NMDA partial agonist) before memory reactivation can facilitate the disruptive effect of PROP and MDZ on fear memory in ETOH rats. Results: We observed a resistance to the disruptive effect of both MDZ and PROP following memory reactivation. Although intra-basolateral amygdala (BLA; 1.25 ug/side) and systemic PROP administration attenuated fear memory in DCS pre-treated ETOH rats, DCS/MDZ treatment did not affect memory in these animals. Finally, a decrease of both total and surface protein expression of the α1 GABAA receptor (GABAA-R) subunit in BLA was found in the ETOH rats. Conclusions: Ethanol withdrawal facilitated the formation of fear memory resistant to labilization post-reactivation. DCS administration promoted the disruptive effect of PROP on memory reconsolidation in ETOH rats. The resistance to MDZ's disruptive effect on fear memory reconsolidation may be, at least in part, associated with changes in the GABAA-R composition induced by chronic ethanol administration/withdrawal.